The Association of Body Image With Anthropometric Measures and Eating Disorders Among Students From University Sports Teams - Nastaran Miri; Mostafa Noroozi; Rosa Zavoshy; Neda Ezzeddin (Shahrekord University of Medical Sciences, 2019)
Background and aims: Body image is defined as a complex concept involving a person's thoughts, feelings, and attitudes about his/her body. The body image dissatisfaction may expose the individuals, specifically athletes, to eating disorders (EDs). The aim of this study is to assess the association of body image score with EDs and anthropometric measures in students from university sports teams. Methods: This cross-sectional study was carried out on 225 students from sports teams of Qazvin University in 2014. The samples were selected by the census method. The Multidimensional BodySelf Relations Questionnaire (MBSRQ), eating attitudes test (EAT-26) questionnaire, and demographic information questionnaire were used for collecting data. Anthropometric characteristics were also measured. The data were analyzed in SPSS software version 22.0. Results: The result of the study showed that the association of body image score with age (P=0.012, OR=0.80, CI=0.179, 1.437) and waist-to-height ratio (WHtR) (P=0.013, OR=-52.14, CI=-93.20, -11.08) was positively significant. Although the mean body image score was lower in students with EDs, it was not statistically significant. In addition, there was not a significant association between body image score and other variables such as marital status, gender, educational level, body mass index (BMI), waist circumference (WC), waist-to-hip ratio (WHR), and hip circumference (HC) (P>0.05). Conclusion: In this study, the body image had a positive significant association with age, and a negative significant one with WHtR. This may indicate that abdominal obesity plays an important role in body image satisfaction among students from the university sports teams.